Transformational Leadership in the Age of AI - C. A., Krishnan (Digital Repository of Theses - SSBM Geneva, 2025)
This research explores the development and validation of an AI blueprint designed to guide leaders in adopting and leveraging the transformative power of Artificial Intelligence (AI). AI, defined as the creation of machines capable of thinking and learning like humans, is driving unprecedented shifts across industries, enhancing efficiency and fostering innovation at an unprecedented scale. Amid this transformation, leadership faces a critical challenge: the lack of a clear, actionable framework to harness AI for sustained success. This study examines leadership in the AI era across three dimensions: individual leadership traits and mindset, organizational building blocks, and foundational resources. It investigates the qualities and cognitive approaches essential for effective leadership in an AI-driven environment, the transformation of business models and functions, and the ethical considerations that underpin organizational success in this context. The research emphasizes the need for a structured framework for AI adoption, given the complexity of integrating AI into business models. The methodology involves a mixed approach, combining qualitative interviews with senior leaders and practitioners across various industries to gather insights into what strategies have succeeded or failed. These findings are supplemented by quantitative research through surveys targeting 262 leaders and mid-level managers. The data collected is analyzed to develop and empirically validate a comprehensive toolkit and roadmap for AI integration. The significance of this research lies in its potential to provide leaders with a reliable, evidence-based blueprint that enhances their ability to navigate the AI age effectively. By advancing industry practice and knowledge, this study aims to equip leaders with the confidence and tools necessary for successful AI-driven digital transformation, ensuring they can manage change effectively and lead their organizations to sustained success. Through hypothesis development, rigorous data collection, and empirical validation, this research aspires to create a roadmap that will serve as a critical resource for leaders facing the challenges and opportunities of the AI era. Keywords: Artificial Intelligence, Transformational Leadership, Organizational Readiness, AI Adoption, Digital Transformation, Strategic Alignment, Change Management, Ethical AI, Data Infrastructure, Innovation Culture